THE STUDY OF TEACHERS’ FEEDBACK IN ONLINE WRITING ASSESSMENT - Hasbullah, Saiyidi; Mistar, Junaidi; Riska Ekawati, Dian Tri (Reflektika, 2020)
Writing is regarded one of the most pivotal English language abilities. Different researchers agree that writing in English as a second or foreign language (ESL/EFL) environment is a challenging process involving social, environmental, motivational, and perceptive concerns. This is really appropriate for the teachers to give some feedbacks to the learners who learn writing using online as the teachers can control and treat the learners based on the ability they have. teacher feedback is an essential part of the process method since it helps students discover their strengths and weaknesses while also motivating them during the writing process. The focus of this research is on the teacher’s feedback during the writing evaluation, as demonstrated by the form, types, platform, and reactions of the students and the reason for the feedback provided. A survey with a quantitative methodology was used in this study. This survey included English teachers from Blitar's vocational high schools. In this study, the purposive sampling approach is applied. Because of their diverse goals and techniques, the researchers chose eight vocational high schools to study. As a result, such schools’ student demographics were diversified. They also required the services of more than one English teacher. Twenty English teachers participated in the poll. Teachers were asked to fill out a questionnaire in order to submit the data. The researchers created closed-ended and open-ended surveys with Google Forms.